Loss of CD30 expression after treatment with brentuximab vedotin in a patient with anaplastic large cell lymphoma: a novel finding. (15th September 2016) - Al‐Rohil, Rami N; Torres‐Cabala, Carlos A; Patel, Anisha; Tetzlaff, Michael T; Ivan, Doina; Nagarajan, Priyadharsini; Curry, Jonathan L; Miranda, Roberto N; Duvic, Madeleine; Prieto, Victor G; Aung, Phyu P
Abstract : Anaplastic large cell lymphoma (ALCL) is an aggressive T‐cell lymphoma characterized by strong and uniform expression of CD30. Brentuximab vedotin (BV), an anti‐CD30 antibody‐drug conjugate has been approved by the U.S. FDA for relapsed/refractory systemic ALCL and achieves improved outcomes. We report a 44‐year‐old African‐American man who presented with lymphadenopathy, lip and chest nodules diagnosed as CD30+, ALK‐negative ALCL. The patient was treated with BV upon recurrence. While on treatment, the patient developed new‐onset nodules on the chest and back. Skin biopsy showed a diffuse dermal infiltrate of medium‐to‐large atypical lymphocytes with frequent mitosis and scattered eosinophils. Immunohistochemically, the atypical cells displayed the same immunophenotype as previous specimens (CD3+, CD4−/CD8−, CD56−, ALK− and TCR γ−), except for lack of CD30 expression which was attributed to BV treatment effect. The diagnosis was thought to be consistent with ALK‐negative ALCL and the patient was continued on BV along with total skin electron beam radiation and the lesions cleared. The patient relapsed 2 months later with extensive disease and expired. In summary, this is the first report in the literature of loss of CD30 expression in ALCL after BV therapy. Awareness of this may prevent a mistaken diagnosis of a CD30‐negative secondary T‐cell lymphoma.